Viral Myocarditis: Classification, Diagnosis, and Clinical Implications - Sozzi, Fabiola B.; Gherbesi, Elisa; Faggiano, Andrea; Gnan, Eleonora; Maruccio, Alessio; Schiavone, Marco; Iacuzio, Laura; Carugo, Stefano (Frontiers in Cardiovascular Medicine, 2022)
Myocarditis is an inflammatory disease of the myocardium with focal or diffuse involvement. Viral infections are the most common causes of myocarditis, especially in the Western Countries. A recent viral illness, with gastroenteric or upper respiratory symptoms, often precedes myocarditis. The absence of specific pathognomonic features in conjunction with the wide spectrum of clinical manifestations that range from subclinical cases to sudden cardiac death makes myocarditis diagnosis particularly challenging. Moreover, myocarditis might represent a cause of initially unexplained dilated cardiomyopathy and heart failure, especially among children and young adults. Cardiac magnetic resonance imaging (CMR) is crucial for myocarditis diagnosis because of its ability to detect interstitial oedema during acute inflammation. The assessment of subepicardial or mid-myocardial fibrosis at late gadolinium enhancement (LGE) is typical of myocarditis. Cardiac arrhythmias are frequent events that may arise especially in more severe myocarditis cases. The most common form of arrhythmia is atrial fibrillation followed by ventricular tachycardia. Documented arrhythmias have been reported more commonly with HIV myocarditis compared to other more common infections such as Adenovirus, Parvovirus B19, human Herpes virus 6, and Enterovirus. The mechanisms of arrhythmogenesis in myocardial inflammation are not fully understood: in the acute phase, the spectrum of arrhythmogenesis ranges from a direct effect on cardiomyocytes, that leads to electrical instability and ion channel impairment, to ischemia from coronary macro or microvascular disease. In chronic myocarditis instead, myocardial replacement with fibrosis promotes scar-mediated re-entrant ventricular arrhythmias. Observational data suggested the important role of CMR, with LGE being the strongest independent predictor of SCD, cardiac and all-cause mortality. In acute myocarditis, the most common localization of subepicardial LGE dwells in the lateral wall. Patients with myocarditis that develop HF and arrhythmias usually show larger LGE distribution, involving several myocardial segments. Moreover, a mid-layer LGE in the interventricular septum is more frequent in acute myocarditis than in acute coronary syndromes cases. The risk of SCD in patients with wide areas of LGE is significant and a shared decision-making approach is warranted. Nevertheless, there is no formal consensus about the extension of LGE to justify implantable cardioverter defibrillator (ICD) implantation in primary prevention.